2019
DOI: 10.1007/s00438-019-01625-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific regulation of neuronal functions in Caenorhabditis elegans: the sex-determining protein TRA-1 represses goa-1/Gα(i/o)

Abstract: Females and males differ substantially in various neuronal functions in divergent, sexually dimorphic animal species, including humans. Despite its developmental, physiological and medical significance, understanding the molecular mechanisms by which sex-specific differences in the anatomy and operation of the nervous system are established remains a fundamental problem in biology. Here, we show that in Caenorhabditis elegans (nematodes), the global sex-determining factor TRA-1 regulates food leaving (mate sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Nematodes were maintained on standard Nematode Growth Medium (NGM) as described previously 69 , 70 , and fed with Escherichia coli OP50 bacteria. The following C. elegans strains were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nematodes were maintained on standard Nematode Growth Medium (NGM) as described previously 69 , 70 , and fed with Escherichia coli OP50 bacteria. The following C. elegans strains were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Nematodes were maintained on standard Nematode Growth Medium (NGM) as described previously 69,70 Prior to performing lifespan assays, VC2552 and VC40319 strains were isogenized by outcrossing 3 times with the wild type.…”
Section: Strains and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three fem genes directly regulate the expression of tra-1 . Loss of function of fem-3 results in the hyperactivity of TRA-1 expression ( Szabó et al, 2009 ; Kutnyánszky et al, 2020 ) and promotes the development of hermaphrodites ( Starostina et al, 2007 ). TRA-1 is orthologous to the human GLI protein, a mediator of Sonic hedgehog signaling, which is involved in embryonic limb development ( Briscoe and Thérond, 2013 ), but also in tumorigenesis ( Coquenlorge et al, 2019 ), and was most recently identified as a suppressor of endometrial stem cell aging ( Cho et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%